THE RELATIONSHIP BETWEEN SELF RELIANCE, PROACTIVE ATTITUDE, AND OPTIMISM WITH COPING STRESS - Anggayani, Luh; Hartawan, I Gusti Made Dharma (Department of Guidance and Counseling, FIP, Undiksha, 2019)
The purpose of this study was to determine the relationship between self-reliance, proactive attitude, and optimism towards coping stress on employees in the Badan Keuangan Daerah Buleleng. This study uses a quantitative approach. Data collection techniques used in this study were in the form of an interval scale questionnaire, where the populations chosen as respondents were all employees in the Badan Keuangan Daerah Buleleng, amounting to 65 people. The data analysis technique used in this study is the SEM (Structural Equation Modeling) structural equation model based on PLSplease (Partial Least Square) variants assisted with SmartPLS 3 software. Proactive attitude has a significant effect on coping stress. Optimism has a significant effect on coping stress. For this reason, in its realization, employees will be able to improve and maintain self-reliance, proactive attitudes, and optimism so that later they will be able to have been well coping stress.